Kecenderungan Global dan Tuntutan Pendidikan Abad Informasi - Bachrudin Musthafa (Universitas Negeri Malang, 2016)
Global communication via internet has offered us virtually limitless access to sources of information across the globe. While its facilitative value is priceless, this technological facility brings with it a set of challenges to educational circles in developing countries like Indonesia. This paper discusses the global trend and its accompanying challenges by outlining some responses other countries have made and posing some orienting quenstions to educational policy makers in Indonesia. Some ideas for human-resource development efforts are poposed and a proposal for systemic educational reform is outlined to invite further thoughts and deliberation